2011
DOI: 10.1029/2010ja015573
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the ionospheric Weddell Sea Anomaly using SAMI2

Abstract: [1] The ionospheric Weddell Sea Anomaly (WSA) was first reported more than five decades ago based on ionosonde data near the Antarctica peninsula. The WSA is an ionospheric structure characterized by a larger nighttime electron density than daytime density. Recent satellite observations indicate that the WSA can extend from South America and Antarctica to the central Pacific. The major physical mechanisms that have been suggested for the WSA formation are an equatorward neutral wind, an electric field, the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 27 publications
10
95
0
Order By: Relevance
“…At ionosphere mid-latitudes, the nighttime electron density enhancement has been observed and reported by previous studies (e.g., Bailey et al 1991;Farelo et al 2002;Dabas and Kersley 2003;Luan et al 2008;Park et al 2008;Chen et al 2011Chen et al , 2012Chen et al , 2013Lin et al 2011;Rajesh et al 2016). This density-enhanced ionospheric feature appeared more frequently during solar minimum conditions (Bailey et al 1991), and it is suggested to be caused by larger downward plasma flux from the plasmasphere during the nighttime (Mikhailov et al 2000;Farelo et al 2002;Dabas and Kersley 2003).…”
Section: Introductionsupporting
confidence: 74%
“…At ionosphere mid-latitudes, the nighttime electron density enhancement has been observed and reported by previous studies (e.g., Bailey et al 1991;Farelo et al 2002;Dabas and Kersley 2003;Luan et al 2008;Park et al 2008;Chen et al 2011Chen et al , 2012Chen et al , 2013Lin et al 2011;Rajesh et al 2016). This density-enhanced ionospheric feature appeared more frequently during solar minimum conditions (Bailey et al 1991), and it is suggested to be caused by larger downward plasma flux from the plasmasphere during the nighttime (Mikhailov et al 2000;Farelo et al 2002;Dabas and Kersley 2003).…”
Section: Introductionsupporting
confidence: 74%
“…This enhancement is associated primarily with meridional winds and magnetic declination (e.g., [12][13][14]). Figure 3 is a summer case where we can see WSA-like variations for data from both sides.…”
Section: Weddell-sea Anomalymentioning
confidence: 99%
“…From the first three-dimensional structure of ionospheric WSA, it can be realized that WSA is simpler part of a bigger ionospheric anomaly, namely, the middle latitude summer nighttime anomaly (MSNA) Chen et al 2011Chen et al , 2013. Meanwhile, the MSNA/WSA eastward movement signature have also been comprehensively studied using F3/C observations Liu et al 2015;Chang et al 2015b) and model simulations Sun et al 2015).…”
Section: Formosat-3/cosmicmentioning
confidence: 99%